Fatores associados ao uso de álcool e drogas por mulheres gestantes - Priscilla Nunes Porto; Silier Andrade Cardoso Borges; Anne Jacob de Souza Araújo; Jeane Freitas de Oliveira; Mariza Silva Almeida; Mayara Novais Pereira (Universidade Federal do Ceará, 2018)
Objective: to verify the association between sociodemographic conditions and the involvement of pregnant women with drugs. Methods: a cross-sectional study was carried out with 268 pregnant women in a public maternity hospital, through an interview. For the bivariate analysis Fisher's Exact Test and odds ratio with 95% confidence interval were used. Results: statistically significant associations were observed between the use of psychoactive substances by pregnant women and schooling (p=0.017), race (p=0.020) and housing condition (p=0.014). Conclusion: it was evidenced that different factors contribute to the occurrence of vulnerability to health among pregnant women, mainly resulting from the integration of individual and social aspects.